KONTRIBUSI KEKUATAN GENGGAMAN TERHADAP AKURASI SERVIS FLAT ATLET TENIS LAPANGAN UNIVERSITAS NEGERI PADANG (PTL UNP) - Arisman, Arisman (STKIP Pasundan, 2018)
The problem with this research is the low accuracy of the flat service of the tennis player when playing, meaning that the flat service punch done by the player is merely hitting the ball into the opponent's service area but does not have clear direction and goals. The low accuracy of flat servicing can be influenced by the grip strength factor, so in this study the authors aim to explain the contribution of grip strength to the accuracy of flat servicing of the tennis court of the State University of Padang (PTL UNP). This research is correlational, which is to find out how much the relationship between variables and contributions made from the independent variables to the dependent variable. The population in this study was the tennis court players in the Padang State University (PTL UNP) Field Tennis Training club and for purposive sampling technique for sampling. To measure the strength of the grip using a dynamometer handgrip tool, while the accuracy of flat service by performing the Hewwit Tennis Achievement Test. So from the results of this study concluded that the accuracy of flat service is influenced by the strength of the grip